Environmental conditions play a key role in controlling the composition and diversity of Colombian biocrust microbiomes - Giraldo-Silva, Ana; Masiello, Caroline A. (Frontiers in Microbiology, 2024)
Drylands soils worldwide are naturally colonized by microbial communities known as biocrusts. These soil microbiomes render important ecosystem services associated with soil fertility, water holding capacity, and stability to the areas they cover. Because of the importance of biocrusts in the global cycling of nutrients, there is a growing interest in describing the many microbial configurations these communities display worldwide. However, comprehensive 16S rRNA genes surveys of biocrust communities do not exist for much of the planet: for example, in the continents of South America and the northern part of Africa. The absence of a global understanding of biocrust biodiversity has lead us to assign a general importance to community members that may, in fact, be regional. Here we report for the first time the presence of biocrusts in Colombia (South America) through 16S rRNA genes surveys across an arid, a semi-arid and a dry subtropical region within the country. Our results constitute the first glance of the Bacterial/Archaeal communities associated with South American biocrust microbiomes. Communities where cyanobacteria other than Microcoleus vaginatus prevail, despite the latter being considered a key species elsewhere, illustrate differentiable results in these surveys. We also find that the coastal biocrust communities in Colombia include halo-tolerant and halophilic species, and that niche preference of some nitrogen fixing organisms deviate from previously described global trends. In addition, we identified a high proportion (ranging from 5 to 70%, in average) of cyanobacterial sequences that did not match any formally described cyanobacterial species. Our investigation of Colombian biocrusts points to highly diverse communities with climatic regions controlling taxonomic configurations. They also highlight an extensive local diversity to be discovered which is central to better design management and restoration strategies for drylands soils currently undergoing disturbances due to land use and global warming. Finally, this field study highlights the need for an improved mechanistic understanding of the response of key biocrust community members to changes in moisture and temperature.